2011
DOI: 10.3184/096034011x13189599518971
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen influenced intergranular crack propagation: analysing microstructure and chemistry in the crack tip region

Abstract: Ni-base superalloys have for decades been studied with regard to environmentally influenced intergranular crack propagation. For high temperature fatigue frequencies 50.1 Hz, it has been shown that an oxygen-rich environment promotes time-dependent crack growth while at 40.1 Hz andyor in inert environments (e.g. vacuum) crack growth is cycle dependent. Oxygen interaction at, or ahead of, the crack tip has been pointed out as the reason for the degraded mechanical properties. While many aspects of this type of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…The crack will tend to propagate along these embrittled grain boundaries faster than the rest of the crack front. This was corroborated by Viskari et al [8]. Additionally, Viskari et al provided a schematic of how uneven oxidation at the crack tip will lead to an uneven crack front, shown in Figure 2.…”
Section: Introductionsupporting
confidence: 63%
“…The crack will tend to propagate along these embrittled grain boundaries faster than the rest of the crack front. This was corroborated by Viskari et al [8]. Additionally, Viskari et al provided a schematic of how uneven oxidation at the crack tip will lead to an uneven crack front, shown in Figure 2.…”
Section: Introductionsupporting
confidence: 63%
“…Li et al [6], have suggested that the sustained load crack growth in RR1000 at 700 • C takes place by a similar mechanism involving the repetitive fracture of an oxide film in the grain boundary ahead of the crack, generally termed stress accelerated grain boundary oxidation -SAGBO [25]. Such films, with penetration depths of around 1-10 µm ahead of the tip, have been observed in dedicated experiments in several Ni-base superalloys [26][27][28]. In the present case, the striation spacing is in the order of 2 µm, which agrees well with the measured oxide intrusion lengths in front of growing cracks in RR1000 (∼1.5 µm) [26] and Allvac 718Plus (∼1 µm) [28].…”
Section: Crack Growth Mechanisms and Threshold For Time-dependent Growthmentioning
confidence: 95%
“…The crack tip oxide films observed in experiments are much thinner than the surface scales used for fracture strain assessment in [30], typically less than 100 nm for growing cracks, and up to 200 nm for tensile loaded but stationary cracks [26,27], although thicker oxides (∼ 1 µm) ahead of slow growing cracks in RR1000 at 700 • C have been observed [6]. At 900 • C the fracture strain increased with decreasing film thickness [30], and assuming a similar relationship at 650 Another potential mechanism that could explain the sustained crack growth is dynamic embrittlement (DE).…”
Section: Crack Growth Mechanisms and Threshold For Time-dependent Growthmentioning
confidence: 99%
“…In [66] Li et al suggested that the sustained load crack growth in RR1000 at 700 ○ C takes place by a mechanism similar to DE by repeated fracture of an oxide film in the grain boundary ahead of the crack, namely SAGBO. Such films, with penetration depths of around 1-10 µm ahead of the tip, have been observed in dedicated experiments in several Ni-base superalloys [63,67,68]. The SAGBO crack propagation mechanism has been discussed and suggested as a possible crack propagation mechanism in in several other papers such as [54,55,59,[69][70][71][72][73][74][75][76][77].…”
Section: Stress Accelerated Grain Boundary Oxidationmentioning
confidence: 82%